Stilistika dalam Puisi “Tasbih” Karya Emha Ainun Nadjib - Rita Novita (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This paper present an analysis of stilistika in poem “Tasbih” Emha uses neutral words with religius meaning. One of the factors that couse of its religiousness arise because of the mulitude of human being who have renounced the religiusness. Furthermore, although it does not countain, but it has a deep meaning. Emha also does too many gramatical irregularities to produce an effect of his poetry.